1993
DOI: 10.2527/1993.713625x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fatty acid composition of subcutaneous adipose tissue from mature Brahman and Hereford cows

Abstract: The fatty acid composition of adipose tissue was measured in 37 mature Brahman and 32 mature Hereford cows to determine breed effect. Diet was held constant among all cows. When biopsied, cows were on oats and native cool-season annual pastures of good quality. Real-time ultrasound measurements of subcutaneous fat were taken at three locations (between the 12th and 13th rib, at the rump, and at the perianal region) to determine overall fatness. Overall fat thickness from these measurements was 1.3 cm for Brahm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 0 publications
4
33
1
6
Order By: Relevance
“…Proportions of C16:0 and C18:0 in intramuscular fat were lower in Thai Native bulls in combination with significantly greater proportions of C18:2n-6, and the longer chain FAs C20:2n-6, C20:3n-6, C22:5n-3 and C22:6n-3. The latter observations are corroborated by Huerta-Leidenz et al (1993) who also reported higher proportions PUFA in adipose tissue of B. indicus v. B. Taurus cattle. The difference in LD FA profile between the two cattle breeds is difficult to explain but an intrinsically higher capacity for deposition of PUFA and conversion to longer chain derivatives in Thai Native cattle compared with Holstein cattle cannot be excluded.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Proportions of C16:0 and C18:0 in intramuscular fat were lower in Thai Native bulls in combination with significantly greater proportions of C18:2n-6, and the longer chain FAs C20:2n-6, C20:3n-6, C22:5n-3 and C22:6n-3. The latter observations are corroborated by Huerta-Leidenz et al (1993) who also reported higher proportions PUFA in adipose tissue of B. indicus v. B. Taurus cattle. The difference in LD FA profile between the two cattle breeds is difficult to explain but an intrinsically higher capacity for deposition of PUFA and conversion to longer chain derivatives in Thai Native cattle compared with Holstein cattle cannot be excluded.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, Huerta-Leidenz et al (1993) reported that proportions of both MUFA and PUFA in adipose tissue were significantly greater in Bos indicus compared with Bos taurus cattle. Interestingly, Laborde et al (2001) reported that the SFA content in Red Angus is higher than in Simmental because of a difference in SCD activity between the two breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, compared to lipids of Brahman steers, those of Hereford steers have a higher proportion of saturated FA (38.8 vs. 34.5% total FA) but lower proportions of monounsaturated (53.4 vs. 59.5%) and polyunsaturated (1.8 vs. 2.4%) FA with both groups of steers being given the same diets. Hereford steers have 5% more FA in fat stores than Brahman steers [48]. The same differences have been reported for intramuscular lipids and cholesterol [110].…”
Section: Effects Of Ruminant Feeding On the Nutritional Value Of Meatssupporting
confidence: 61%
“…Breed differences and associated effects of maturity or growth potential on the subcutaneous or intramuscular fatty acid composition of beef were also reported by Gillis et al [28], Huerta-Leidenz et al [32,33], Malau-Aduli et al [45,46], Mills et al [52], Pitchford et al [63], Rule et al [73] and Siebert et al [80]. Sex effects are also reported regularly.…”
Section: Beefmentioning
confidence: 59%